Troubleshooting SharePoint : the complete guide to tools, best practices, PowerShell One-Liners, and scripts - Simpkins, Stacy (Apress, 2017)
Utilize a treasure trove of free SharePoint troubleshooting tools and receive insightful guidance about the types of SharePoint issues that can be discovered through their use. Chapters in this book contrast solid and least privileged builds in order to help you understand the types of issues that are raised when farms are not built the least privileged way. Because SharePoint errors often present themselves one way, when an issue is actually something entirely different, the process of finding the root cause can feel like going down a rabbit hole. Hands-on exercises get you comfortable with logs so you can efficiently and effectively "explore the rabbit hole." Troubleshooting SharePoint also demonstrates how to identify components and settings that enter an environment where access has been restricted. The author shares his proven methods for researching an issue based on what appears in the logs, with the understanding that often it is not as simple as asking a question, but how you ask it that leads to the right answer. What You'll Learn: Utilize networking tools such as NetMon, WireShark, and Fiddler for troubleshooting Master SharePoint PAL, Webalizer, Indihaing, Developer Dashboard, the Feature Admin tool, and more Become proficient using Timer Jobs and Search Diagnostics Understand how various files are accessed by IIS sites and within the server file system Discover how IIS mappings and file permissions affect issues Troubleshoot with ULS Viewer, PowerShell, and tools such as ProcMon, PerfMon, and Event Viewer Meet your new best friend, the ULS Viewer Use Event Viewer as a troubleshooting source Become conversant in the "language" of SharePoint from the log's perspective This book is for SharePoint administrators and developers who want to learn how to quickly diagnose and resolve issues in any SharePoint server in SharePoint farms where admin access is possible. Stacy Simpkins is a SharePoint Engineer with the leading managed cloud company, Rackspace. He is passionate about SharePoint and loves helping people get the most out of it. Stacy holds multiple Microsoft certifications and often blogs (Another SharePoint Blog) and presents on the topic of SharePoint. He leads the Tampa Bay SharePoint user group